(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: To describe the level of physical activity students at Hanoi Medical University are now engaging in in 2022 and conduct some associated factor analysis. Methods: A cross-sectional descriptive study on 306 students of Hanoi Medical University using the IPAQ-SF toolkit. Classification and assessment of physical activity based on IPAQ-SF and WHO recommendations. Results: Among the study subjects, 39 students (12.8%) were physically active at a high level, 118 students were moderately active (38.6%) and 149 students were active at a low level (48.7%). Only 35.3% of students are physically active in accordance with WHO recommendations. Physical activity was statistically significantly correlated to 4 factors gender, school year, BMI, and significance. Conclusion: Students at Hanoi Medical University continue to exhibit comparatively low levels of mental activity. The school may take action to increase extracurriculars that incorporate physical activity, like sports clubs.